A general strategy to generate oxygen vacancies in bimetallic layered double hydroxides for water oxidation. Issue 21 (22nd February 2023) - Wu, Konglin; Shi, Luoxiang; Wang, Zhendong; Zhu, Ye; Tong, Xinyue; He, Wenxiang; Wang, Junwei; Zheng, Lirong; Kang, Yanshang; Shan, Weilong; Wang, Zhiguo; Huang, Aijian; et al.
Abstract : The NiFe layered double hydroxide with abundant oxygen vacancies (Ov2 -NiFe hydroxide) induced by C3 N4 exhibits improved OER performances compared with the NiFe hydroxide. Abstract : A general electrocatalyst design for water splitting through generating oxygen vacancies in bimetallic layered double hydroxides by using carbon nitride is proposed. The excellent OER activity of the achieved bimetallic layered double hydroxides is attributed to oxygen vacancies, which reduce the energy barrier of the rate-determining step.